Physical Measurement and Subjective Survey for Thermal Comfort Assessment in the Laboratories of Faculty Civil Engineering and Built Environment - Hamzan, Fikri Hakim; Zakaria, Mohd Azuan (Recent Trends in Civil Engineering and Built Environment, 2024)
Laboratory is the room for student practice the skill and handle the material and apparatus testing but activities in laboratory require a certain level of metabolic rate and suitable apparel and a good level of indoor thermal condition should carefully to prevent thermal dissatisfaction. The research was aimed at finding the level of thermal comfort and indoor air conditioned of an undergraduate laboratory classes in the Main Campus, University Tun Hussein Onn Malaysia. A field measurement was conducted to measure the indoor thermal condition of laboratories room which is physical measurement and subjective survey had been conducted at three laboratories in Faculty of Civil Engineering and Built Environment. Physical measurement, the parameters measured were air temperature, relative humidity, globe temperature and wind speed while subjective survey parameter is thermal sensation and thermal preference occupants. So, the activities during laboratory class for all laboratories can be conclude as discomfort for current temperature by adjusting to suitable temperature for all activities to ensure the comfort condition for all selected laboratories.